Do princípio ao fim, o amor: a errância erótica de Cassandra Rios - Santos, Ivanildo da Silva (2020)
Over the centuries, writers and philosophers have tried to explain in their writings the nature, origin and reasons for love, however, they have always come up against something of the order of the insurmountable. But in examining the nature of love, they were able to decipher some of its mysteries. As the greatest exponent, Freud (1914/2010) defends love as a mirage in an idealized one. That is, the lover invests all libido in an object that, for him, is his everything. Later, the theme started to be taken up by renowned psychoanalysts, such as Jacques Lacan (1985) and J. D. Nasio (1997). The first founds Eros as what the subject does not have, therefore it is not. The primary consequence of this approach, the desire for lack. For Lacan (1985), Eros, son of Poverty, is the search to fill a gap and try to restore itself to a unit. What would contribute to apprehend the love myth as the conversion of the impossible, since the fullness of the two beings will never be reached. Thus, the lost object is what love most seeks. In turn, Nasio (1997) states that the more you love, the more you suffer. It is in this line of investigation that the present work is inserted, however, seeking to analyze the lesbian love experience in a literary text produced by a lesbian writer. Thus, we propose to examine the novel A Borboleta Branca (1974), written by Cassandra Rios, whose main objective is to try to analyze lesbian love and its specificities. The work is divided into three chapters: in the first, it seeks to distinguish the main socio-historical influences on love relationships based on philosophy, literature and sociology. In the second, the psychoanalytical contributions on the love phenomenon are investigated. The third chapter, on the other hand, traces considerations about the characters, space and plot of the novel, establishing data involving love and female homosexuality.